2015
DOI: 10.1117/12.2081772
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of mass detection performance in contrast enhanced digital mammography

Abstract: We address the detectability of contrast-agent enhancing masses for contrast-agent enhanced spectral mammography (CESM), a dual-energy technique providing functional projection images of breast tissue perfusion and vascularity using simulated CESM images. First, the realism of simulated CESM images from anthropomorphic breast software phantoms generated with a software x-ray imaging platform was validated. Breast texture was characterized by power-law coefficients calculated in data sets of real clinical and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…However, simulated breast CT reconstructions showed that phantom realism was lacking, and the authors suggested that further development in modeling fibroglandular tissue structure was needed to improve realism. This phantom has been evaluated by both power‐law analysis as well as a two‐alternative forced choice (2‐AFC) psychophysical study comparing simulated and real images . To improve the realism of fibroglandular tissue structure of this phantom, Li et al .…”
Section: Digital Anthropomorphic Phantomsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, simulated breast CT reconstructions showed that phantom realism was lacking, and the authors suggested that further development in modeling fibroglandular tissue structure was needed to improve realism. This phantom has been evaluated by both power‐law analysis as well as a two‐alternative forced choice (2‐AFC) psychophysical study comparing simulated and real images . To improve the realism of fibroglandular tissue structure of this phantom, Li et al .…”
Section: Digital Anthropomorphic Phantomsmentioning
confidence: 99%
“…This phantom has been evaluated by both power-law analysis as well as a two-alternative forced choice (2-AFC) psychophysical study comparing simulated and real images. 57 To improve the realism of fibroglandular tissue structure of this phantom, Li et al 58 developed a 3D breast texture model to simulate FFDM and DBT images representing the population of women seen in clinical practice. The model emulated the small-and medium-scale fibroglandular and interglandular breast tissue, and it was based on segmented clinical bCT images.…”
Section: C6 Other Digital Breast Phantomsmentioning
confidence: 99%
“…Phantom image realism has been extensively assessed by statistical image properties [17], [31]- [33] and to a lesser extent by psychophysical experiments [25], [34], [35]. The more extensive reporting using statistical image properties can be attributed to the practicality of the objective measures, while psychophysical experiments involving humans are time consuming.…”
mentioning
confidence: 99%
“…In terms of psychophysical experiments, "fool-thereader" evaluations have been proposed [25], [34], [35], aiming to measure the ability of human observers to distinguish simulated phantom images from clinical images. To our knowledge, there are no publications evaluating task-driven phantom texture realism.…”
mentioning
confidence: 99%
“…Diante de tais limitações, é comum que pesquisadores criem suas próprias bases de imagens (NISHIKAWA, 1996;WARREN et al, 2007;WU et al, 2014) Diversas outras pesquisas (BERKS et al, 2010;BLIZNAKOVA et al, 2003;CARTON et al, 2015;CHEN et al, 2017;SAUNDERS et al, 2006;WARREN et al, 2013) têm sido direcionadas à elaboração de phantoms computacionais gerando imagens sintéticas.…”
Section: Cadxunclassified